2021
DOI: 10.1186/s12964-020-00691-x
|View full text |Cite
|
Sign up to set email alerts
|

PVT1 signals an androgen-dependent transcriptional repression program in prostate cancer cells and a set of the repressed genes predicts high-risk tumors

Abstract: Background Androgen receptor (AR) and polycomb repressive complex 2 (PRC2) are known to co-occupy the loci of genes that are downregulated by androgen-stimulus. Long intergenic non-coding RNA (lincRNA) PVT1 is an overexpressed oncogene that is associated with AR in LNCaP prostate cancer cells, and with PRC2 in HeLa and many other types of cancer cells. The possible involvement of PVT1 in mediating androgen-induced gene expression downregulation in prostate cancer has not been explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…These PVT1 isoforms are transcribed by different promoters [63], therefore, they have to be considered separate transcriptional entities although possibly interconnected. lncPVT1 is enriched in the nucleus versus the cytosol [19,65,66], as observed by subcellular fractionation and subsequent RT-qPCR [19,[65][66][67][68], and RNA fluorescence in situ hybridisation [69,70] in several cancer cell lines. Interestingly, lncPVT1 is described as a chromatin modifier [71].…”
Section: Two Molecules Same Function?mentioning
confidence: 84%
“…These PVT1 isoforms are transcribed by different promoters [63], therefore, they have to be considered separate transcriptional entities although possibly interconnected. lncPVT1 is enriched in the nucleus versus the cytosol [19,65,66], as observed by subcellular fractionation and subsequent RT-qPCR [19,[65][66][67][68], and RNA fluorescence in situ hybridisation [69,70] in several cancer cell lines. Interestingly, lncPVT1 is described as a chromatin modifier [71].…”
Section: Two Molecules Same Function?mentioning
confidence: 84%
“…Alternatively, lncRNAs can regulate nuclear positioning of enhancer, potentiating the enhancer to induce expression of the target genes. Others have shown that distinct lncRNAs interact with the chromatin remodeler PRC2 complex, resulting in methylation of histone H3 at lysine 27 (H3K27me3) and repression of gene transcription [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PVT1 is a widely reported lncRNA in PCa which is over-expressed and related to an unwilling prognosis ( Yang et al, 2017 ; Liu et al, 2021 ). Videria et al ( Videira et al, 2021 ) found that PVT1 may participate in an AR-dependent transcriptional repression program in PCa cells. They demonstrated that 160 genes repressed by AR were up-regulated and the epigenetic markers such as H3K27me3 and H3K27ac were remodeled when PVT1 was silenced.…”
Section: Ar Pathwaymentioning
confidence: 99%